Some Epidemiological Aspects Of Subfertile Women Who Underwent Laparoscopy - Deeba, Farzana; Alam, ABM Muksudul; Ava, Nilufar Nasrin; Islam, Md. Rafiqul; Matin, Abdul; Khan, Rita (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: Epidemiological aspects of sitbfertile women underwent laparoscopy. Place of Study: This retrospective study was done in the Obstetrics and Gynaecology Department of Bangladesh Medical College hospital. Duration: July 2003 to June 2004. Study Population: Women suffering from primarv and secondary subfertility, who had under gone laparoscopy. Total 61 patient had laparoscopy for evaluation of subfertility. No documents were available for 6 patient and they were excluded from the study. Result: The study group comprises 55 cases of which 67.37% was of primary and 32. 73", was of secondary subfertility. Professional women group (56.4%) was higher than housewife group (43.6%). In this study 11.11% had history of spontaneous abortion and 33.33% had history of MR. In this study menstrual period was within 7 days in 70.9% cases and in 10.9% cases were more than 7 days, in 14.54% cases menstrual cycle was more than 35 days and in 3.64% cases were less than 22 days. 40% of the patient did not used any contraceptive. Conclusion: The number of subfertility visits' has increased in the last few rears because of increasing awareness for available services and option for resolving subfertilitv. Prompt investigation and appropriate referral allow a couple to receive advice and treatment to help them reach their goal. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 6-9 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12343